Modelling an economic relationship for macroeconomic determinants of Malaysian housing prices / Marziah Mokhtar, Sabariah Yusoff and Muhammad Danial Samsuddin - Mokhtar, Marziah; Yusoff, Sabariah; Samsuddin, Muhammad Danial (Universiti Teknologi MARA, 2021)
The issue of housing affordability is increasingly becoming a phenomenon as property prices in Malaysia have risen beyond the reach of most people. Hence, the objective of the study is to investigate key macroeconomics determinants that trigger the upward movement of housing prices in Malaysia. The paper also seeks to establish the best fit economic model, that represents the relationship between housing prices and its macroeconomics determinants. Four economic models are proposed in depicting the economic relationship between house price index, which acts as proxy for housing prices, and macroeconomic determinants namely gross domestic product (GDP), interest rate (INT), inflation rate (INF) and exchange rate (ER). The Exponential Model is selected to be the most fit model for the data of 30-year period covering 1989 till 2018. Diagnostic tests are conducted to identify the existence of statistical problem of multicollinearity and autocorrelation, and hence steps are taken to rectify them accordingly. The analytical results show that gross domestic product (GDP), interest rate (INT) and exchange rate (ER) are all positively significant macroeconomic variables that explain the volatility of housing prices in Malaysia. However, the inflation rate (INF), which negatively affect the housing prices is not a significant variable.